2011
DOI: 10.1007/s10115-011-0463-8
|View full text |Cite
|
Sign up to set email alerts
|

Data preprocessing techniques for classification without discrimination

Abstract: Recently, the following Discrimination-Aware Classification Problem was introduced: Suppose we are given training data that exhibit unlawful discrimination; e.g., toward sensitive attributes such as gender or ethnicity. The task is to learn a classifier that optimizes accuracy, but does not have this discrimination in its predictions on test data. This problem is relevant in many settings, such as when the data are generated by a biased decision process or when the sensitive attribute serves as a proxy for uno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
793
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 935 publications
(799 citation statements)
references
References 19 publications
(28 reference statements)
2
793
0
4
Order By: Relevance
“…Some authors [11,17] study how to prevent data mining from becoming itself a source of discrimination. In this paper, instead we focus on the data mining problem of detecting discrimination in a dataset of historical decision records, and in the rest of this section, we present the most relevant literature.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors [11,17] study how to prevent data mining from becoming itself a source of discrimination. In this paper, instead we focus on the data mining problem of detecting discrimination in a dataset of historical decision records, and in the rest of this section, we present the most relevant literature.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, we observed that, as for when the ordering of the nodes is provided as an input, Algorithm 2 first constrains the current solution for Suppes' conditions (Lines [12][13][14][15][16][17] and then performs the maximum likelihood estimation of the DAG by hill climbing (Lines 19-29). But this time, these steps are iterated along the neighbor orders by an outer hillclimbing procedure (Lines 5-10 and 31-33).…”
Section: Learning the Temporal Ordering Of Variablesmentioning
confidence: 99%
“…Data preprocessing methods [1,12,13,17,21,37,43] modify the historic data to remove discriminatory effect according to some discrimination measure before learning a predictive model. For example, in [17] several methods for modifying data were proposed.…”
Section: Discrimination Preventionmentioning
confidence: 99%
“…Data preprocessing methods [1,12,13,17,21,37,43] modify the historic data to remove discriminatory effect according to some discrimination measure before learning a predictive model. For example, in [17] several methods for modifying data were proposed. These methods include Massaging, which changes the labels of some individuals in the dataset to remove discrimination, Reweighting, which assigns weights to individuals to balance the dataset, and Sampling, which changes the sample sizes of different subgroups to make the dataset discrimination-free.…”
Section: Discrimination Preventionmentioning
confidence: 99%
See 1 more Smart Citation